Lead poisoning linked to occupational exposure - case reports - Kościuk, Andrzej; Kos, Michał; Drankowska, Justyna; Tchórz, Michał (Journal of Education, Health and Sport, 2019)
Introduction: Lead is one of the oldest widely used industrial metals. Throughout the ages, its significant toxicity caused poisoning of exposed people. Even today occupational exposure remains a significant hazard.Aim: The aim of the study is to depict the risk associated with lead exposure on the base of the case report.Methods: Patient’s medical history analysis and the review of available literature.Results: Two patients with history of occupational lead exposure were admitted to hospital. Their symptoms suggested chronic lead poisoning. Blood lead level was excessive in both cases. The patients were treated with antioxidants and advised to reduce their exposure to lead, with continuing ambulatory therapy. Conclusions: All known effects of Pb are extremely harmful to humans. Lead poisoning still appears to be a problem in some jobs and environments, particularly in cases of chronic low level exposure. Proper monitoring of workplace conditions and regular medical checkups for those at risk should be practiced to avoid cases of chronic poisoning in the future.